Developing a spreadsheet-based simulator for solar rooftop installation assessment - Rahmat M.A.A.; Mohamed H.; Zuhdi A.W.M.; Roslan M.E.B.M. (American Institute of Physics Inc., 2024)
This paper reports the development of the spreadsheet-based simulator for Solar Rooftop Installation Assessment. The aim of this paper is to develop a simulator that can design a solar photovoltaic (PV) requirement on a rooftop building in Malaysia. The results and parameters of the developed simulator are tested and validated with a commercial software, Helioscope. Several sets of simulations by using the simulator are conducted at different specifications of panel by considering parameters such as the number of panels installed, output power and energy produced from the PV system. Other simulations at different methods of finding an area are conducted to validate the simulator with Helioscope online platform. The results of the simulations indicate that lengthwise across orientation offered a higher number of panels installed, output power generated, and energy produced compared to the lengthwise up orientation. The sizing calculation had decreased the estimated value of the simulation result to become the final value, especially on the model Sharp NU-AK300B with 5.74% of the percentage difference between its estimated value and final value. The comparison between different methods of finding an area presents that method 1 at 60% total area which located in the lengthwise across category and method 1 at 90% total area which located in the lengthwise up category with both of them had the smallest percentage of area covered on their respective category, shows the highest accuracy of the simulation result which is 1.3% percentage error for method 1 (60% total area) and 42.86% percentage error for method 1 (90% total area). Meanwhile, for maximum value category, the comparison of the method used with the Helioscope (without keepouts) result is much accurate which is 32.58% percentage error compared to the comparison with Helioscope (with keepouts) which is 51.94% percentage error. 2023 AIP Publishing LLC.